Student Participation in Online Discussions - Hew, Khe Foon. author. aut Link
XIV, 142 p.
Keywords: The increasingly prevalent use of online- or blended-learning in schools and universities has resulted in the asynchronous online discussion forum becoming a common means of facilitating dialogue between instructors and students, as well as between students and students, beyond the boundaries of the physical classroom. This book provides a comprehensive review of previous research studies in order to identify the prevalent factors leading to limited student contribution in online discussion forums. To set the research in context, nine exploratory case studies are presented and procedures to implement the solutions provided. This book is distinctive and results-focused, unlike others tackling this topic. Using empirically-based methodologies, the book clearly and succinctly provides up-to-date infomration on a previosuly under-represented area of research. For once, the focus is squarely on student/peer facilitation rather than teacher facilitated or heavily text based discussion.